Student's Reflections on Teil Based Materials and Digital Media in Learning World Englishes - Muhammad Al Haq Bayyin; Nurul Apriani; Hilma Fitriana; Aidil Syah Putra (Sean Institute, 2026)
This study aims to explore students’ reflections on the use of Teaching English as an International Language (TEIL)-based materials and digital media in learning World Englishes. The study seeks to understand how TEIL-oriented instruction influences students’ awareness of English diversity, learning engagement, intercultural understanding, and challenges encountered during the learning process. A qualitative phenomenological approach was employed. The participants were six fifth-semester students of the English Education Study Program at the Faculty of Teacher Training and Education. Data were collected through classroom observations, documentation of students’ assignments and presentations, and semi-structured interviews. The data were analyzed using thematic analysis.The results indicate that the use of TEIL-based materials and digital media contributed positively to students’ learning experiences. Students developed awareness of English diversity, showed higher engagement in learning, increased intercultural awareness, and gained confidence in using English. However, students also experienced difficulties in understanding unfamiliar English varieties, particularly non-standard accents and expressions. The findings highlight the significance of TEIL-based instruction in preparing students for global communication while emphasizing the need for pedagogical guidance and gradual exposure. This study concludes that TEIL-based materials and digital media are effective in supporting World Englishes learning. Future research is recommended to involve larger participant groups and examine instructional strategies for addressing challenges in understanding English diversity.